2016
DOI: 10.15252/emmm.201606210
|View full text |Cite
|
Sign up to set email alerts
|

The amyloid hypothesis of Alzheimer's disease at 25 years

Abstract: Despite continuing debate about the amyloid β‐protein (or Aβ hypothesis, new lines of evidence from laboratories and clinics worldwide support the concept that an imbalance between production and clearance of Aβ42 and related Aβ peptides is a very early, often initiating factor in Alzheimer's disease (AD). Confirmation that presenilin is the catalytic site of γ‐secretase has provided a linchpin: all dominant mutations causing early‐onset AD occur either in the substrate (amyloid precursor protein, APP) or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

65
4,131
3
40

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 4,767 publications
(4,239 citation statements)
references
References 127 publications
(165 reference statements)
65
4,131
3
40
Order By: Relevance
“…Inflammation is centrally involved in AD pathogenesis, as denoted by the presence of activated microglia and astrocytes as well as the increased levels of inflammatory molecules in the brain. A β 42 is the key neurotoxic and pro‐inflammatory component in AD,7, 8 but recent studies have also pointed toward a potential anti‐inflammatory role for A β 42 under certain conditions 13, 14. Since ApoE is the major mediator of A β clearance from the brain,44 we wanted to address potential changes in the plasma concentration of A β among different APOE groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is centrally involved in AD pathogenesis, as denoted by the presence of activated microglia and astrocytes as well as the increased levels of inflammatory molecules in the brain. A β 42 is the key neurotoxic and pro‐inflammatory component in AD,7, 8 but recent studies have also pointed toward a potential anti‐inflammatory role for A β 42 under certain conditions 13, 14. Since ApoE is the major mediator of A β clearance from the brain,44 we wanted to address potential changes in the plasma concentration of A β among different APOE groups.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, A β peptides of 42 amino acids in length (A β 42) are considered the key mediators of synaptotoxicity and neurotoxicity in AD 7. According to the prevailing amyloid‐cascade hypothesis, A β deposition in the brain triggers the hyperphosphorylation of tau and its accumulation as neurofibrillary tangles, activation of inflammatory cells and pathways, initiation of oxidative stress, and decline in synaptic and neuronal health and finally neurodegeneration 8. This view recently gained further support from the identification of a protective APP variant (A673T), which was later shown to reduce A β levels and protect against cognitive decline 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the prevention and treatment of AD is a major unmet medical need. The amyloid hypothesis posits that the abnormal accumulation of amyloid-β (Aβ) peptides in the brain, and their aggregation, is an essential feature of AD (2,3); however, results from clinical studies using several Aβ-targeting compounds have called into question the existence of a direct link between a reduction in Aβ and improvement of brain function, particularly in more advanced disease stages (4)(5)(6). In addition, recent evidence obtained in mouse models carrying genetic mutations that cause AD in humans revealed that immunotherapy with antibodies against Aβ worsened rather than reversed neuronal dysfunction (7).…”
mentioning
confidence: 99%
“…N eurodegenerative diseases are highly complex disorders characterized by extensive neuronal dysfunction, which is typically associated with protein misfolding and aggregation (1)(2)(3)(4)(5)(6)(7)(8)(9). A feature common to essentially all of these conditions is the presence of abnormal protein deposits, including amyloid plaques and neurofibrillary tangles in Alzheimer's disease (AD) and Lewy bodies in Parkinson's disease (PD) (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…A feature common to essentially all of these conditions is the presence of abnormal protein deposits, including amyloid plaques and neurofibrillary tangles in Alzheimer's disease (AD) and Lewy bodies in Parkinson's disease (PD) (1)(2)(3)(4)(5)(6)(7)(8)(9). It is increasingly recognized that the formation of such deposits, rather than being an unusual process involving only a small number of proteins, may represent a widespread phenomenon (1), with hundreds of different proteins found to aggregate under stress conditions, in aging, or in disease (5,(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%